2019
DOI: 10.22159/ijms.2019.v7i4.34408
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice of Generic Drugs Among Doctors in a Tertiary Care Hospital

Abstract: Objectives: Generic medicines constitute an important aspect of affordable health care. “JAN AUSHADHI” campaign was started by the Government of India in 2008 to support generic prescriptions. Recently, medical council of India had requested all clinicians for generic prescriptions. With this background, this study was undertaken to evaluate the knowledge, attitude, and practice of generic medicines among doctors. Methods: It was a cross-sectional, prospective, questionnaire-based study. After obtaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…Prasad et al reported that about 61% doctors permitted the patients to substitute generic for a brand or vice-versa and reported that 49.0% patients disapproved the generic substitution. 27,28 The pricing strategies of medicines in Lebanon had also a great influence in promoting generic drugs because these strategies pressure the pharmaceutical companies to lower the price of the brand name drugs to compete with the generics which therefore discourage generic substitution for those drugs whose prices have become similar to their generic equivalents. Consequently, we have an inappropriate medicine prices and pricing systems to promote generic medicine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prasad et al reported that about 61% doctors permitted the patients to substitute generic for a brand or vice-versa and reported that 49.0% patients disapproved the generic substitution. 27,28 The pricing strategies of medicines in Lebanon had also a great influence in promoting generic drugs because these strategies pressure the pharmaceutical companies to lower the price of the brand name drugs to compete with the generics which therefore discourage generic substitution for those drugs whose prices have become similar to their generic equivalents. Consequently, we have an inappropriate medicine prices and pricing systems to promote generic medicine.…”
Section: Discussionmentioning
confidence: 99%
“…6 Some studies propose essential suggestions to promote generic drug substitution which include the presence of supportive regulations promoting a competitive market for generic drugs, creation of a trusted regulatory authority for medicines, capacity of quality assurance, and acceptance by health professional and the public. 21,3032 Also, the removing of incentives to use branded drugs as a way to increase prescription of generic medicines as suggested in a Danish study. 33 Using the active ingredient for prescribing could be a good suggestion to increase the promotion of generics.…”
Section: Discussionmentioning
confidence: 99%
“…reported that 49.0% patients disapproved the generic substitution. [ 29 31 ] This study reported about 61% physicians strongly agreed or agreed that generics are equally effective as brand. The study results were at par with the studies reported by Singh et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 25 26 ] Contrarily, literature search also shows a few studies conducted in India with inadequate knowledge and perception of the doctors towards the generics. [ 27 28 29 30 ] As there was inconsistency with the evidence, this study was planned to assess knowledge and perception of generic drugs among doctors. Objective was to study knowledge and perception about generic drugs among the practicing primary care physicians and highlight the factors influencing practice of prescription of generics.…”
Section: Introductionmentioning
confidence: 99%
“…Oleh sebab itu apoteker harus memiliki pengetahuan dan sikap yang baik terhadap obat generik untuk dapat mendukung penggunaanya. Pada beberapa penelitian yang pernah dilakukan menunjukkan bahwa terdapat pengetahuan dan sikap yang beragam terhadap obat generik, apoteker komunitas di Karachi Pakistan memiliki pengetahuan baik, apoteker komunitas di Kuwait memiliki pengetahuan kurang, dan sebanyak 46,79% dokter di Tertiary Care Hospital memiliki pengetahuan cukup (Al Hussaini et al, 2018;Jamshed et al, 2010;Prasad et al, 2019). Kemudian penelitian terdahulu juga menunjukkan bahwa sebagian besar apoteker di Palestina dan Kuwait memiliki sikap positif, sedangkan apoteker komunitas di Karachi Pakistan memiliki sikap beragam (Al Hussaini et al, 2018;Jamshed et al,2010;Shraim et al, 2017).…”
unclassified